Internal debt and welfare - Zarko Y. Kalamov (Journal of Public Economic Theory, 2022)
This paper analyzes how multinational firms' internal debt financing affects high-tax countries. It uses a dynamic small open economy model and takes into account that internal debt impacts both the multinational firms' investment decisions and the government's tax policy. The government has incentives to redistribute income from firm owners to workers. If the government's redistributive motive is not too strong, internal debt reduces welfare in the short term by decreasing tax revenues. However, debt financing stimulates capital accumulation and exerts a positive long-term welfare impact.
Keywords: 330